I‘m doing an exercise where a particle $A$ with mass $m_A$ decays into two particles $B$ and $C$ with mass $m_B$ and $m_C$. The goal is to calculate the absolute value of the momentum of the particles $B$ and $C$. In the solution they start with ($E$ is the energy) $$(m_Ac,0,0,0)=(E_B/c,0,0,p)+ (E_B/c,0,0,-p)$$ and when the square it they get: $$m_A^2c^2=m_B^2c^2+ m_C^2c^2+2(E_BE_C/c^2+|p|^2)$$ But if I calculate the square I get at the end $-|p|^2 $ and not $|p|^2$ because of the minkowski metric. So where is my mistake?


1 Answer 1


With $E_B = \sqrt{p^2+m_B^2}$ and $E_C = \sqrt{p^2+m_C^2}$:

$$\begin{align}\begin{pmatrix}\sqrt{p^2+m_B^2} + \sqrt{p^2+m_C^2}\\ 0 \\ 0 \\ 0\end{pmatrix}^2 &= \left(\sqrt{p^2+m_B^2} + \sqrt{p^2+m_C^2}\right)^2\\ &=m^2_B + m^2_C + 2p^2 + 2 \underbrace{\sqrt{p^2+m_B^2}}_{E_B}\underbrace{\sqrt{p^2+m_C^2}}_{E_C} \end{align}$$


$$ \begin{align} \sqrt{p^2+m_B^2}\sqrt{p^2+m_C^2} &= \frac{m_A^2 - 2p^2 - m^2_B - m^2_C}{2}\\ (p^2+m_B^2)(p^2+m_C^2) &=\frac{\left(m_A^2 - 2p^2 - m^2_B - m^2_C \right)^2}{4}\\ \end{align} $$

From there it follows that

$$p=\frac{\sqrt{m_A^4 - 2 m_A^2 m_B^2 + m_B^4 - 2 m_A^2 m_C^2 - 2 m_B^2 m_C^2 + m_C^4}}{2 m_A}$$

This can be simplifed by using the Källén function

$$\lambda(a,b,c) = a^2+b^2+c^2-2(ab+bc+ca)$$


$$p = \frac{\sqrt{\lambda(m_A^2, m_B^2, m_C^2)}}{2m_A}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.